Power-Sharing as The Key of Secessionist Conflict Resolution in Developing Democratic Countries - Jati, Wasisto Raharjo (Jurnal Politik, 2021)
This article explains how power-sharing could determine conflict resolution in develo¬ping states, particularly in developing countries. This scheme offers a win-win solution between state actors and the separatist movements to curb conflict and initiate pe¬ace-building at the grassroots level. Using a quantitative analysis that employed data¬sets from Power-Sharing Event Dataset (PSED) and Implementation of Pacts Dataset (IMPACT), this article notably reveals two important findings. First, the most promising power-sharing schemes are territorial and political power-sharing. Furthermore, the preliminary talk about ideal power-sharing consensus between the state actors and rebel groups is important to determine the outcome of power-sharing policies. Finally, this article concludes that the state capacity shows the final conflict resolution. Strong states can manage ethnic conflict, while weak state capacity could exacerbate the ethnic conflict.